FEATURES OF AUDITS IN THE BANKING SECTOR - Azizbek Matchanov (PEDAGOGS, 2025)
Abstract. The article demonstrates some of the features of audits in banks. The topic is relevant due to the fact that the difficult economic situation has damaged the country’s economy. Entrepreneurs are trying to save money on many processes, including mandatory audits. At the same time, the external audit of the bank is extremely important for the entire national economy, there should be no inaccuracies in it. The conclusion of the article indicates the need to study the presented prospects and proposals for implementation in practice.